FAKTOR-FAKTOR YANG MEMOTIVASI PARTISIPASI KERJA IBU RUMAH TANGGA DALAM MENINGKATKAN EKONOMI KELUARGA - Elly Karmeli; Inda Julisatina (Pusat Riset dan Publikasi, 2023)
This study aims to determine the factors that motivate the work participation of housewives in improving the family economy. This research was conducted on fishing housewives in Sumbawa Regency. The type of research used in this research is associative research. The type of data used is quantitative data obtained directly from the source. The population in this study was the fishermen community in Labuhan Jambu, Tarano District, totaling 1,015 people, while the determination of the sample used the Slovin technique so that the number of samples was 91 people. Data was collected using a questionnaire. Data analysis was performed using multiple linear regression analysis techniques, partial and simultaneous hypothesis testing, and testing the coefficient of determination (R2) through SPSS software version 16.0 for windows. The results of this study indicate that (1) the level of education has a positive and significant effect on the participation of housewives in improving the economy of fishermen's households (2) the number of family dependents has a positive and significant effect on the participation of housewives in improving the economy of fishermen's households (3) the level of education and the number of family dependents have a significant effect on the participation of housewives in improving the fishermen's household economy.